Presymptomatic and longitudinal neuroimaging in neurodegeneration: from snapshots to motion picture - a systematic review - HARDIMAN, ORLA; BEDE, PETER (My University, 2015)
Background Recent quantitative neuroimaging studies have been successful in capturing phenotype and genotype-speci fi c changes in dementia syndromes, amyotrophic lateral sclerosis, Parkinson ’ s disease and other neurodegenerative conditions. However, the majority of imaging studies are cross-sectional, despite the obvious superiority of longitudinal study designs in characterising disease trajectories, response to therapy, progression rates and evaluating the presymptomatic phase of neurodegenerative conditions. Objectives The aim of this work is to perform a systematic review of longitudinal imaging initiatives in neurodegeneration focusing on methodology, optimal statistical models, follow-up intervals, attrition rates, primary study outcomes and presymptomatic studies. Methods Longitudinal imaging studies were identi fi ed from ‘ PubMed ’ and reviewed from 1990 to 2014. The search terms ‘ longitudinal ’ , ‘ MRI ’ , ‘ presymptomatic ’ and ‘ imaging ’ were utilised in combination with one of the following degenerative conditions; Alzheimer ’ s disease, amyotrophic lateral sclerosis/motor neuron disease, frontotemporal dementia, Huntington ’ s disease, multiple sclerosis, Parkinson ’ s disease, ataxia, HIV, alcohol abuse/ dependence. Results A total of 423 longitudinal imaging papers and 103 genotype-based presymptomatic studies were identi fi ed and systematically reviewed. Imaging techniques, follow-up intervals and attrition rates showed signi fi cant variation depending on the primary diagnosis. Commonly used statistical models included analysis of annualised percentage change, mixed and random effect models, and non-linear cumulative models with acceleration – deceleration components. Discussion and conclusions Although longitudinal imaging studies have the potential to provide crucial insights into the presymptomatic phase and natural trajectory of neurodegenerative processes a standardised design is required to enable meaningful data interpretation
IN_PRESS
Keywords: neurodegenerative conditions; neurodegenerative conditions; Ageing; Genes & Society; Neuroscience; Next Generation Medical Devices